INFLUENCE OF SOME NATURALLY GROWING LOCAL HERBS IN DUHOK-KURDISTAN REGION- IRAQ ON THE MORTALITY OF WAX MOTH Galleriea Mellonella L. LARVAE - MOHAMEED, VIYAN GHAZI (Journal of Duhok University, 2020)
The effect of some naturally growing local herbs from Gara Mountains in Duhok-Kurdistan region-Iraq on the mortality of wax moth (Galleria mellonella L. larvae were investigated in the laboratory using two different methods, first; spraying combs with the plant extract, second; directly smoking with dried herbs the larvae. During the first day, five hours after treatment, higher percentage of mortality were appeared in larvae fed on sprayed wax with Soryas (15 %) in June, (15%) in July, while larvae fed on Jater showed the highest percentage (22%) in August. Five days after treatment, higher percentage of mortality were found in larvae fed on sprayed wax with Jater (88 %) and with Soryas (82%) in August. Five hours after smoking, Strk (61 %) was the most effective than other plants, followed by Jater (55%) and Soryas (54 %). higher percentage of mortality was found two days after smoking in larvae treated with Jater (90 %) in June and (86%) in July. All tested plants were effective in controlling Galleria mellonella larvae, they showed during the experiment of smoking more than (80%) mortality of larvae four days after the treatment. Soryas and Jater were the most effective tested plants while Hnkdan was the least one.